Ramayana - Rajagopalachari, C. (Mumbai : Bharatiya Vidya Bhavan, 2021)
Here is a new Clay Sanskrit Library publication of the middle book of Valmiki's Ramayana, the source revered throughout South Asia as the original account of the career of Rama, the ideal man and the incarnation of the great god Vishnu." "After losing first his kingship and then his wife, Sita, Rama goes to the monkey capital of Kishkindha to seek help in finding her, and meets Hanuman, the greatest of the monkey heroes. The brothers Valin and Sugriva are both claimants for the monkey throne; in exchange for the assistance of monkey troops in discovering where Sita is held captive, Rama has to help Sugriva win the throne. The monkey hordes set out in every direction to scour the world, but they have no success until an old vulture tells them Sita is in Lanka. The book concludes with Hanuman's preparation to leap over the ocean to Lanka to pursue the search." "The tragic rivalry between the two monkey brothers is in sharp contrast to Rama's affectionate relationship with his own brothers, and forms a self-contained episode within the larger story of Rama's adventures. Rama's intervention in the struggle between Sugriva and Valin is the chief moral focus of the book.
Keywords: Epic literature; Epic poetry